Why and how the publication of the Pastoral Liturgy Directory turned 2023 into a seismic year for RE in Catholic schools in England and Wales - Whittle, Sean (Journal of Religious Education, 2024)
This article presents an initial analysis of the Prayer and Liturgy Directory, which was published by the Catholic Education Service of England and Wales in 2023. It is argued that this document has many positive features, and provides a helpful guidance document for those involved with planning liturgies in a Catholic school context. However, a closer analysis indicates that there are some problematic features with this document. This analysis of the Prayer and Liturgy Directory (2023) is set against a broader claim, which argues that it is very significant for RE and Catholic Education because of its relationship to two other documents that come to the fore in 2023. In retrospect 2023 will turn out to be a watershed point that has set RE in English and Welsh Catholic schools along a highly distinctive pathway.